Opening the black box of transfer systems in public sector health services in a Western state in India. Issue 1 (December 2016) - Purohit, Bhaskar; Martineau, Tim; Sheikh, Kabir
Abstract Background Limited research on Posting and Transfer (P&T) policies and systems in the public sector health services and the reluctance for an open debate on the issue makes P&T as a black box. Limited research on P&T in India suggests that P&T policies and systems are either non-existent, weak, poorly implemented or characterized by corruption. Hence the current study aimed at opening the "black box" of P&T systems in public sector health services in India by assessing the implementation gaps between P&T policies and their actual implementation. Methods This was a qualitative study carried out in Department of Health, in a Western State in India. To understand the extant P&T policies, a systems map was first developed with the help of document review and Key Informant (KI) Interviews. Next systems audit was carried out to assess the actual implementation of transfer policies by interviewing Medical Officers (MOs), the group mainly affected by the P&T policies. Job histories were constructed from the interviews to understand transfer processes like frequencies of transfers and to assess if transfer rules were adhered. The analysis is based on a synthesis of document review, 19 in-depth interviews with MOs working with state health department and five in-depth interviews with Key Informants (KIs). Framework analysis approach was used to analyze data using NVIVO. Results The state has a generic transfer guideline applicable to all government officers but there is no specific transfer policy or guideline for government health personnel. The generic transfer guidelines are weakly implemented indicating a significant gap between policy and actual implementation. The formal transfer guidelines are undermined by a parallel system in which desirable posts are attained, retained or sometimes given up by the use of political connections and money. MOs' experiences of transfers were marked by perceptions of unfairness and irregularities reflected through interviews as well as the job histories. Discussion The generic transfer rules and ambiguity in how transfers are treated may explain the discrepancy between policy and implementation leading to systems abuse. This discrepancy could have negative influence on MOs' morale which could in turn affect distribution of MOs. Where possible, ambiguity in the rules should be avoided and a greater transparency on implementation of the transfer rules is needed. However, it may not be possible to make any significant improvements to P&T policies and how they are implemented until the external pressure that creates parallel systems is greatly reduced in translating HR policy into HR practice. Conclusions Effective P&T policies and implementation may have important implications for organizational performance and may help to improve Human Resource (HR) policy and HR expertise. Also there is a greater need for transparency on implementation of the rules. However, it may not be possible to make any significant improvements to P&T policies and how they are implemented until the external pressure that creates parallel systems is greatly reduced.